Formulasi Kebijakan Roadmap Inovasi Daerah di Kabupaten Bekasi - Waluyo Zulfikar; Ipah Ema Jumiati (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2020)
Bekasi Regency is the area with the largest industrial area in Southeast Asia, where there are 16 industrial areas with relatively large land area. In addition, there are also seven large industrial zones or industrial zones on an international scale, in line with this, the problem of public service delivery in the Bekasi District Government must be carried out properly to the public. In optimizing the public services, various innovative ideas and ideas are needed to create synergy and efficiency in the provision of these public services. In this study, the innovation system is a unified component that influences the direction of development and speed of innovation, diffusion, and learning processes in the development, mastery, advancement and application/utilization of science and technology. How sub-subsystems (elements / factors) play their roles, their interrelations (including policy coherence), and the dynamics of their interactions determine or influence the dynamic performance of innovation systems. Strengthening the innovation system means structuring the system (holistic, simultaneous, systemic issues) in a structured way. In a policy perspective, strengthening innovation systems means remedial steps that need to be directed to address systemic failures. Therefore, policy strategies need to be developed as a unified innovation policy framework (KKI) to strengthen the system.